Positive feedback effect of PGE2 on cyclooxygenase-2 expression is mediated by inhibition of Akt phosphorylation in human follicular dendritic cell-like cells. (July 2017) - Choe, Jongseon; Yoon, Yongdae; Kim, Jini; Jung, Yu-Jin
Highlights: PGE2, PGF2α, and beraprost stimulate COX-2 expression in human FDC-like cells. PGE2 and beraprost, but not PGF2α, reduce Akt phosphorylation in HK cells. PGE2 and beraprost, but not PGF2α, induce COX-2 expression by inhibiting Akt phosphorylation in HK cells. Abstract: Prostaglandins (PGs) are bioactive lipid mediators generated from the phospholipids of cell membrane in response to various inflammatory signals. To understand the potential role of PGs in PG production itself during immune inflammatory responses, we examined the effect of PGE2, PGF2α, and beraprost on COX-2 expression using follicular dendritic cell (FDC)-like HK cells isolated from human tonsils. Those three PGs specifically augmented COX-2 protein expression in a dose-dependent manner after 4 or 8 h of treatment. The enhancing effect was also reflected in the actual production of PGs and the viable cell recovery of germinal center B-cells. To investigate the underlying molecular mechanism, we examined the impact of PI3K inhibitors on PG-induced COX-2 expression. Interestingly, COX-2 induction by PGE2 and beraprost, but not PGF2α, was enhanced by wortmannin and LY294002. In line with this result, Akt phosphorylation was inhibited by PGE2 and beraprost but not by PGF2α . The distinct effect of PGE2 and beraprost from PGF2α was reproduced in Akt-knockdowned HK cells. Our current findings imply that PGE2 and PGI2 stimulate COX-2 expression in FDC by inhibiting Akt phosphorylation. Additional studies are warranted to determine the potential role of Akt as a therapeutic target in patients with inflammatory disorders.